Regular orbits of finite primitive solvable groups, the final classification. (May 2023) - Holt, Derek; Yang, Yong
Abstract: Suppose that a finite solvable group G acts faithfully, irreducibly and quasi-primitively on a finite vector space V, and G is not metacyclic. Then G always has a regular orbit on V except for a few "small" cases. We completely classify these cases in this paper.